The challenges of reducing solid waste production among University student : myth or reality / Siti Nur Amirah Syarafana Mat Sim@ Mat Hussin and Noorazlina Kamarulzaman - Mat Sim@ Mat Hussin, Siti Nur Amirah Syarafana; Kamarulzaman, Noorazlina (2023)
Producing solid waste is a major environmental problem that is getting worse as urbanisation and population increase take root. In Malaysia, it is getting tougher to find places for proper waste disposal, and the vast majority of those that are already there are virtually out of their useful lives. The poor recycling rate in Malaysia which is currently only about 31% is one of the key factors contributing to disposal sites' hastened demise. In order to increase the rate of waste reduction, collaboration between the community, the informal sector, the official waste collectors, and the government is required. People's awareness of this issue needs to be taken into consideration, so this article will present data on the investigation of awareness of the importance in reducing solid waste production in the nation among college students and explore the difficulties faced by college students at UiTM Seri Iskandar, Perak, to do so. The preparation and distribution of a survey form for data collecting utilising online methods and applying quantitative and qualitative method. The research reveals the level of awareness and the actual difficulty college students encountered in not putting waste reduction into practise. College management play an important role to reduce the obstacles including implement educational programmeand improve the waste facilities.